The role of emotional intelligence for teacher's efficacy and classroom management - Valente, Sabina (2022)
In recent years, several studies have revealed multiple benefits of teachers’ emotional intelligence (EI) concerning their professional performance, regarding teaching and learning process, student's school performance, job satisfaction, reduction of stress and burnout, and the importance of interpersonal relationships at school. However, few studies have explored how teachers’ EI capacity affects their efficacy for teaching and classroom management. The aim of this study was twofold: to examine the relationship between teachers’ EI ability's, teacher efficacy, and classroom management, and to analyze the relationship between teacher’s characteristics (gender) and professional background (service time and academic formation) and teacher’s EI ability's. 634 Portuguese teachers filled out a form with personal and professional data and answered an adaptation of the Emotional Skills and Competence Questionnaire, and the Teacher Efficacy in Classroom Management and Discipline Scale. Structured Equation Model analyses were computed and showed that teachers who tended to have higher levels of ability to perceive, express and manage emotions reported higher levels of teaching effectiveness and classroom management effectiveness. Therefore, is important for Portuguese teachers to develop their emotional skills during academic formation, for a more effective professional activity.